Composition of some indigenous economic tree species in Yorro, Taraba State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the composition of some indigenous economic tree species in Yorro Local Government Area (LGA) of Taraba State, Nigeria. The objectives were to identify indigenous edible tree species and evaluate the proximate composition of the most prevalent species. Data were obtained using a semi-structured questionnaire and laboratory analysis. A sample intensity of 40% was used to select four districts at random. A total of 398 respondents were sampled using Solvin's formula and the Snowball sampling method. Vitellaria paradoxa and Ziziphus mauritiana were purposively selected to elicit information on proximate composition. Matured fresh undamaged parts of these species were harvested, sun-dried, and ground into powder form for laboratory analysis. Data obtained were analyzed using proximate parameters (protein, moisture content, crude fiber, ash content, lipid, and carbohydrates) and statistical tools (frequencies, percentages, ANOVA, and LSD). The results indicated that most respondents were married (58.79%), middle-aged (48.99%), male (53.52%), and had a primary education (31.66%). They engaged in farming (49.25%) and the utilization of indigenous economic tree species for medicinal (21.36%) and trade purposes (15.08%). The respondents identified a total of 23 indigenous economic tree species, with Ziziphus mauritiana being the most prevalent (95.98%). The proximate findings showed the exceptional amount of carbohydrates (89.24±0.148% and 384.29±5.742%) in Vetellaria. paradoxa and Ziziphus mauritiana roots, respectively. Similarly, the protein (35.34±0.652%) and lipid (33.73±1.092%) contents were high in Ziziphus mauritiana and Vetellaria paradoxa seeds, respectively. These attributes indicate the potential significance of these species in the food and pharmaceutical industries. There is an urgent need to implement sustainable management solutions for these species.